Modeling Patient-Specific Muscular Dystrophy Phenotypes and Therapeutic Responses in Reprogrammed Myotubes Engineered on Micromolded Gelatin Hydrogels - Barthélémy, Florian; Santoso, Jeffrey W.; Rabichow, Laura; Jin, Rongcheng; Little, Isaiah; Nelson, Stanley F.; McCain, Megan L.; Miceli, M. Carrie (Frontiers in Cell and Developmental Biology, 2022)
In vitro models of patient-derived muscle allow for more efficient development of genetic medicines for the muscular dystrophies, which often present mutation-specific pathologies. One popular strategy to generate patient-specific myotubes involves reprogramming dermal fibroblasts to a muscle lineage through MyoD induction. However, creating physiologically relevant, reproducible tissues exhibiting multinucleated, aligned myotubes with organized striations is dependent on the introduction of physicochemical cues that mimic the native muscle microenvironment. Here, we engineered patient-specific control and dystrophic muscle tissues in vitro by culturing and differentiating MyoD–directly reprogrammed fibroblasts isolated from one healthy control subject, three patients with Duchenne muscular dystrophy (DMD), and two Limb Girdle 2A/R1 (LGMD2A/R1) patients on micromolded gelatin hydrogels. Engineered DMD and LGMD2A/R1 tissues demonstrated varying levels of defects in α-actinin expression and organization relative to control, depending on the mutation. In genetically relevant DMD tissues amenable to mRNA reframing by targeting exon 44 or 45 exclusion, exposure to exon skipping antisense oligonucleotides modestly increased myotube coverage and alignment and rescued dystrophin protein expression. These findings highlight the value of engineered culture substrates in guiding the organization of reprogrammed patient fibroblasts into aligned muscle tissues, thereby extending their value as tools for exploration and dissection of the cellular and molecular basis of genetic muscle defects, rescue, and repair.